A byte at a time: Africa’s progress towards a digital agriculture future - Glatzel, Katrin; Hendriks, Sheryl L. (Jeune Afrique Media Group, 2019)
Over the past two decades, Africa has overcome multiple obstacles to economic growth and eradicating poverty, registering a widespread progress. The gradual transformation of Africa’s food systems has been key to this process, but to sustain and accelerate growth—particularly in the face of demographic changes, urbanization, shifting diets, climate change and protracted humanitarian crises—a new set of innovative solutions is urgently needed.